BREEDER'S PERCEPTIONS OF GOVERNMENT'S POLICY REGARDING VACCINATION FOR FOOT AND MOUTH DISEASE (FMD) IN BEEF CATTLE (Case Study in Tikung District, Lamongan Regency) - Sumartono; Badat Muwakhid; Dyah Wahyuning (Jurnal Ternak, 2024)
The cause of Foot and Mouth Disease (FMD), FMD virus (FMDV), is an acute infectious disease that is highly contagious in hoofed animals. In Lamongan Regency, outbreaks of FMD in cattle have led to a decline in population. Despite vaccination programs, breeders' willingness to vaccinate is influenced by perceptions of vaccine safety and effectiveness. Increasing vaccination coverage is hoped to restore FMD-free status in the area. This study aims to provide knowledge about the influence of breeders' perceptions of government policy on FMD vaccination of beef cattle in Tikung Sub-district, Lamongan Regency and to provide knowledge about the factors that influence breeders' perceptions of government policy on FMD vaccination of beef cattle in Tikung Sub-district, Lamongan Regency. This study is a mixed methods study with a sequential explanatory design. The instruments in this study included questionnaires and interview guidelines with data collection techniques of questionnaire distribution and in-depth interviews with informants. While data analysis techniques in the quantitative approach were carried out with univariate and bivariate analysis. And the qualitative approach was carried out using the interactive model according to Miles et al. The results of the study showed that there was a significant positive effect of breeders' perceptions on FMD vaccination policy in beef cattle in Tikung Subdistrict, Lamongan District (significance value of 0.000 (0.000 < 0.05) and t value of 5.894 > t table (1.9858 )). Factors such as extensive knowledge of FMD and vaccination programs, personal experience with the disease, and support from the government and livestock groups contribute to positive perceptions of these policies. However, challenges such as concerns about post-vaccination side effects and timing conflicts with breeders' village activities affect participation rates and trust in the program.